2011
DOI: 10.1063/1.3644157
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Co2MnAl Heusler compound for anomalous Hall effect sensors

Abstract: Sets of Heusler compound Co2MnAl thin films were grown on MgO (100) and Si (100) substrates by radio frequency magnetron sputtering. Composition, magnetic, and transport properties were studied systematically for samples deposited at different conditions. In particular, the anomalous Hall effect resistivity presents an extraordinarily temperature independent behavior in a moderate magnetic field range from 0 to 0.6 T. We analyzed the off-diagonal transport at temperatures up to 300 °C. Our data show the suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(21 citation statements)
references
References 20 publications
0
19
2
Order By: Relevance
“…The anomalous Hall conductivity (σ xy0 ) value is defined as the difference in σ xy values at zero and the saturation fields. It is found that σ xy0 attains a value of 162 S/cm, which is higher than that observed in Mn 2 CoAl (22 S/cm) [2], but less than that of the half-metallic Co 2 FeSi (200 S/cm at 300 K) [25], and Co 2 MnAl (2000 S/cm) [26]. As can be seen from the inset of Fig.…”
Section: Electrical Conductivity and Hall Measurementsmentioning
confidence: 67%
“…The anomalous Hall conductivity (σ xy0 ) value is defined as the difference in σ xy values at zero and the saturation fields. It is found that σ xy0 attains a value of 162 S/cm, which is higher than that observed in Mn 2 CoAl (22 S/cm) [2], but less than that of the half-metallic Co 2 FeSi (200 S/cm at 300 K) [25], and Co 2 MnAl (2000 S/cm) [26]. As can be seen from the inset of Fig.…”
Section: Electrical Conductivity and Hall Measurementsmentioning
confidence: 67%
“…Table 2 shows that the calculated σ A x y and σ S x y are large for Co 2 MnAl, Co 2 MnGa and Co 2 MnIn, but are five to ten times smaller for the other compounds. This suggests that Co 2 MnAl, Co 2 MnGa and Co 2 MnIn may find applications in, e.g., magnetic sensors [26]. Interestingly, the calculated σ S…”
Section: Anomalous and Spin Hall Conductivitiesmentioning
confidence: 82%
“…Therefore, the principal purpose of this work is to understand the AHE in Co-based full Heusler compounds, especially those of half-metallic ones. The results may also help experimentally search for the Heusler compounds with a large AHE for applications, e.g., in magnetization sensors [26].…”
Section: Introductionmentioning
confidence: 96%
“…5 The compound Co 2 MnAl (x ¼ 1) has not been predicted to be fully spin-polarized; however, its high Curie temperature of $700 K, 3,6 combined with its large anomalous Hall effect (AHE), 7 has redeemed it as a valuable material for Hall effect sensors in automotive applications. 8 In light of the above mentioned potential applications of the full-stoichiometric compounds, it is worthwhile to investigate the physical properties of Co 2 MnSi 1-x Al x as a function of Al content. The dependence of the magnetic and structural properties of Co 2 MnSi 1-x Al x on Al content has been previously investigated.…”
mentioning
confidence: 99%